Motorized wheelbarrow - Amirul Firdaus, Abu Samah (2021)
This thesis introduces a motorized wheelbarrow aimed at improving the design of the conventional wheelbarrow. It consists of wheelbarrow, hub motor, linear actuator and weight sensor. The hub motor is used to improve the wheelbarrow handling that can move it easily when going up or down the slope. It uses a linear actuator to ease the unloading process. The reading of the weight is measured and detected by weight sensor and Arduino UNO as a microcontroller in this system. It using 3 tires to stable the wheelbarrow when moving forward, backward or rotating the other direction. The PWM motor driver as a controller that control the speed and direction of rotation of motor.